Consolidated Drained Triaxial Test on Treated Coastal Soil and Finite Element Analysis Using PLAXIS 2D - Zahraalsadat Elias Lankaran; Nik Norsyahariati Nik Daud; Vahid Rostami; Zainuddin Md. Yusoff (Advances in Materials Science and Engineering)
Coastal areas are susceptible to erosion and accretion; therefore, coastal soil mechanical properties and ability to withstand loads are important factors to consider. Coastal erosion is inevitable as the sand and silt particles move inexorably from place to place. This study investigates the primary consolidation behaviour of treated coastal soil by comparing the empirical data obtained from triaxial tests based on analytical calculations and FEM software, PLAXIS 2D. The aim is to propose an optimum mixture to improve coastal soil’s geotechnical properties, especially in shear strength and stiffness. Two different material models, including lime/RHA and cement/RHA, were utilized to compare the performance of advanced constitutive treated soil samples against the Mohr–Coulomb material model. 8% lime and rice husk ash (portions of 1 : 2) were chosen to be replaced with cement, as an application of waste material can reduce the cost and environmental impact. All the triaxial tests were conducted at effective confining pressures of 50 kPa, 100 kPa, and 200 kPa. While using PLAXIS 2D, the asymmetrical condition for modelling the triaxial test and 15 nodded triangular elements, as well as the Mohr–Coulomb model for soil properties, are used to simulate the empirical data to verify this study’s effectiveness. The modelling of 2-dimensional drain behaviour involves setting out the model geometry and boundary conditions. The results revealed that the deviatoric stress and volumetric changes of LRHA increased in a range of 4.5 to 5.2% and 72.18 to 141.79%, respectively, as compared to CRHA. The FE analysis results for peak deviator stress values reasonably agree with the experimental results. The variation was in the range of 1.22% to 4.10%. Eventually, the treated soil’s peak and maximum shear strengths are reported to allow flexible use in future projects.